The Rasch Model Analysis: Cases Study in SDGs Trend Point 7 in Physics Learning Based Domicile - Rahmatta Thoriq Lintangesukmanjaya; Agus Mifthakhul Rizka; Adrian Bagas Damarsha; Dwikoranto (The Journal of Indonesia Sustainable Development Planning, 2025)
The low level of environmental awareness among the younger generation, particularly the understanding of the importance of clean and affordable energy, is a serious challenge to the desired efforts. This research aims to explore the understanding and motivation of high school students related to clean and affordable energy sources, in accordance with the 2030 Sustainable Development Goals (SDGs). The results of Rasch model analysis show that students' understanding of clean energy varies, with students in urban areas having better access to information compared to students in districts. There are differences in understanding based on gender, female students tend to have difficulty understanding energy problems than male students. Female students tend to be more motivated in clean energy and environmental issues, while male students have a stronger understanding of sustainable technology. Real projects and interactive materials that connect clean energy with daily life through physics learning motivate learners. These findings underscore the importance of inclusive and project-based education to increase student awareness and participation in supporting the achievement of the 2030 SDGs in sustainable physics learning.